.6(10x-2)+3=2-(3x+4)

Simple and best practice solution for .6(10x-2)+3=2-(3x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .6(10x-2)+3=2-(3x+4) equation:


Simplifying
0.6(10x + -2) + 3 = 2 + -1(3x + 4)

Reorder the terms:
0.6(-2 + 10x) + 3 = 2 + -1(3x + 4)
(-2 * 0.6 + 10x * 0.6) + 3 = 2 + -1(3x + 4)
(-1.2 + 6x) + 3 = 2 + -1(3x + 4)

Reorder the terms:
-1.2 + 3 + 6x = 2 + -1(3x + 4)

Combine like terms: -1.2 + 3 = 1.8
1.8 + 6x = 2 + -1(3x + 4)

Reorder the terms:
1.8 + 6x = 2 + -1(4 + 3x)
1.8 + 6x = 2 + (4 * -1 + 3x * -1)
1.8 + 6x = 2 + (-4 + -3x)

Combine like terms: 2 + -4 = -2
1.8 + 6x = -2 + -3x

Solving
1.8 + 6x = -2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
1.8 + 6x + 3x = -2 + -3x + 3x

Combine like terms: 6x + 3x = 9x
1.8 + 9x = -2 + -3x + 3x

Combine like terms: -3x + 3x = 0
1.8 + 9x = -2 + 0
1.8 + 9x = -2

Add '-1.8' to each side of the equation.
1.8 + -1.8 + 9x = -2 + -1.8

Combine like terms: 1.8 + -1.8 = 0.0
0.0 + 9x = -2 + -1.8
9x = -2 + -1.8

Combine like terms: -2 + -1.8 = -3.8
9x = -3.8

Divide each side by '9'.
x = -0.4222222222

Simplifying
x = -0.4222222222

See similar equations:

| -1+1x=5 | | 60+4x-1=6x+11 | | 4t+10s=250 | | 31+7x=16 | | 4x^2-33x+33=-9+6 | | (2x-7)=117 | | 3x-3-2x+2=5 | | 5=7-2 | | 12+5p=6p+12 | | 8v+5=7v+17 | | X^4+4x^3=12x^2 | | 1m=12.4 | | (15x-5)=(90-4x) | | 14+2x=7x-11 | | 4x^5-11=-20491 | | tnx=1.5 | | 8(a-2)+7=6-4(a+3) | | (5n+1)(3n-2)=0 | | 12(x+1)=6(2x+1)+6 | | 12X^3+20x^2-15x-25=0 | | -6(w+2)-w-3=-7(w+5)+20 | | 60+2x+y=360 | | (5v-7)(6-v)=0 | | 3p+q^3=7 | | 4y+6x=124 | | 4x+3x=180 | | 16x+4x^2=128 | | (x+7)(x-3)=5 | | 4x(5x+2x)=52 | | .5x-2=2x-23 | | 6:2(1+3)=? | | xy-4x=19 |

Equations solver categories